ON THE LEGAL DEFINITION OF SOME PROBLEMS URBAN DEVELOPMENT - , І. І., С. Г. (Municipal economy of cities. Series: «Economy science», 2013)
Considered the most pressing areas of problem solving relationship interests authorities, businesses and individuals in the course of urban development.